2010
DOI: 10.1073/pnas.1000604107
|View full text |Cite
|
Sign up to set email alerts
|

Combined niche and neutral effects in a microbial wastewater treatment community

Abstract: It has long been assumed that differences in the relative abundance of taxa in microbial communities reflect differences in environmental conditions. Here we show that in the economically and environmentally important microbial communities in a wastewater treatment plant, the population dynamics are consistent with neutral community assembly, where chance and random immigration play an important and predictable role in shaping the communities. Using dynamic observations, we demonstrate a straightforward calibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
439
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 509 publications
(467 citation statements)
references
References 37 publications
26
439
1
1
Order By: Relevance
“…This view is supported by studies of replicate aquatic microcosms inoculated from different environmental sources; after 3 weeks' development, the final communities were no more similar than the starting communities, and inter-replicate variation was high (Langenheder et al, 2006). Similar results have been reported for community development in simple hypolithic communities in desert environments (Caruso et al, 2011), wastewater treatment plants (Ofiteru et al, 2010), replicate laboratory phototrophic biofilms (Roeselers et al, 2006) and laboratory-scale wetlands (Baptista et al, 2008). It is important to note, however, that variable final community composition may be associated with stable broad-scale ecosystem function (Fernández et al, 1999;Langenheder et al, 2006).…”
Section: Introductionsupporting
confidence: 73%
“…This view is supported by studies of replicate aquatic microcosms inoculated from different environmental sources; after 3 weeks' development, the final communities were no more similar than the starting communities, and inter-replicate variation was high (Langenheder et al, 2006). Similar results have been reported for community development in simple hypolithic communities in desert environments (Caruso et al, 2011), wastewater treatment plants (Ofiteru et al, 2010), replicate laboratory phototrophic biofilms (Roeselers et al, 2006) and laboratory-scale wetlands (Baptista et al, 2008). It is important to note, however, that variable final community composition may be associated with stable broad-scale ecosystem function (Fernández et al, 1999;Langenheder et al, 2006).…”
Section: Introductionsupporting
confidence: 73%
“…At high dispersal, within-group distance decreased. High dispersal rates are thought to lead to communities overwhelmed by mass effects that can alter the importance of stochasticity on microbial community composition (Ofiteru et al, 2010;Adams et al, 2014). Our model allows us to distinguish between two possible outcomes of mass effects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ofiteru et al (2010) studied communities in wastewater treatment plants that are subject to high dispersal rates, and found that deterministic selection had little influence on microbial community composition, and was instead driven by neutral dynamics (drift and random immigration). In lakes, high immigration rates rarely overwhelm local selection (Jones and McMahon, 2009;Logue and Lindström, 2010) but can cause local communities to become more similar to the composition of communities immigrating (for example, from a stream inlet) (Lindström et al, 2006;Crump et al, 2007;Adams et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…T Caruso et al enhance niche-selection processes (Chase, 2007;Ofiteru et al, 2010). The important novelty is that a key component of the equation appears to be the differences in patterns of community structure for the functional groups that form the system (phototrophs and heterotrophs).…”
Section: Desert Microbial Community Assemblymentioning
confidence: 99%
“…Conversely, more deterministic processes driven by species interaction and niche partitioning are predicted to produce segregation in terms of species co-occurrence or even aggregation (Chave, 2004;Dornelas et al, 2006;Chase, 2007), if niche partitioning interacts with environmental stochasticity (that is, disturbance regime) or with extreme changes in key abiotic variables such as water availability and temperature. Theories have been tested against communities with a single trophic level including microorganisms (Volkov et al, 2003(Volkov et al, , 2004Dumbrell et al, 2010;Ofiteru et al, 2010) and recently by manipulating relatively simple systems such as aquatic bacterial communities (Bell, 2010). Community assembly is highly dependent on a multitude of bottom-up and top-down trophic influences, which depend upon a biological diversity encompassing multiple phyla and realms.…”
Section: Introductionmentioning
confidence: 99%